Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/(sici)1097-4644(20000801)78:2<251::aid-jcb8>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Binding motifs ofCBP2 a potential cell surface target for carcinoma cells

Abstract: Previously we have shown (Hebert et al. [1999] J. Cell Biochem. 73:248-258) that among many cell lines the CBP2 gene product, Hsp47, eludes its retention receptor, erd2P, resulting in the appearance of Hsp47 on the cell surface associated with the tetraspanin protein CD9. Since Hsp47 possesses a highly restricted binding cleft, random peptide display libraries were used to characterize peptides binding to Hsp47 and then to target this protein on carcinoma cell lines in vitro. Comparison of the clones obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Regarding this later potential, an important advantage is that HSP47 has procollagen as its exclusive target, though it is important to consider that HSP47 is expected to locate in the cytosol, cycling between ER compartments and Golgi complex, and an effective delivery system is needed. However, previous studies have demonstrated that cell lines derived from head and neck cancers may express HSP47 in the cell surface anchored to CD9 16,29 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding this later potential, an important advantage is that HSP47 has procollagen as its exclusive target, though it is important to consider that HSP47 is expected to locate in the cytosol, cycling between ER compartments and Golgi complex, and an effective delivery system is needed. However, previous studies have demonstrated that cell lines derived from head and neck cancers may express HSP47 in the cell surface anchored to CD9 16,29 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, each of these targets has ligands that can be used to actively target SPIO nanoparticles. Specifically, HER2 affibody, cyclic RGD, and the LDS affinity peptide ( Table 1 ) were selected as ligands for targeting HER2/neu, αvβ 3 integrin, and HSP47 respectively 29 30 31 32 33 34 . A set of four lanthanide-doped SPIO nanoparticles (Ho, Sm, Gd, and Er) were synthesized.…”
mentioning
confidence: 99%
“…Only a modest amount of time, effort, and resources are needed to screen a library displaying a billion different peptides GENERAL CONSIDERATIONS by affinity selection. Peptide ligands have been isolated to a wide array of proteins, such as 14-3-3 proteins (1, In this article, we present simple, step-by-step proto-2), calmodulin (3)(4)(5), cell surface receptors (6-10), EH cols for screening phage-displayed combinatorial pepdomains (11)(12)(13), heat-shock proteins (14,15), integrins tide libraries. Many types of protein targets, including (16), PDZ domains (17,18), SH3 domains (19)(20)(21), vasenzymes (34,35), have been used successfully to affinity cular endothelial growth factor (VEGF) (22, 23), viral select binding phage.…”
mentioning
confidence: 99%